2002
DOI: 10.1021/la020290s
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B−Dipalmitoyl Phosphatidyl Glycerol Interactions Responsible for the Reduced Toxicity of Liposomal Formulations:  A Monolayer Study

Abstract: Mixtures of amphotericin B (AmB) and dipalmitoyl phosphatidyl glycerol (DPPG) were studied as floating Langmuir monolayers at the air/water interface. The films were analyzed using surface pressure-area (π-A) isotherms and compressional modulus-surface pressure (Cs -1 -π) plots in addition to Brewster angle microscopy. The film components were found to interact with each other with the strongest interactions occurring at the ca. 2:1 AmB:DPPG mixed film composition (XAmB ) 0.66), suggesting the formation of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Although the monolayer experiments for mixtures of AmB and sterols/lipids have already been published [3,13,[30][31][32][33][34]36] in none of these studies was dimethylformamide (DMF) used to dissolve all the molecules investigated. The spreading solvent affects the shape of AmB isotherms as well as the stoichiometry of the antibiotic/sterol complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Although the monolayer experiments for mixtures of AmB and sterols/lipids have already been published [3,13,[30][31][32][33][34]36] in none of these studies was dimethylformamide (DMF) used to dissolve all the molecules investigated. The spreading solvent affects the shape of AmB isotherms as well as the stoichiometry of the antibiotic/sterol complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown from toxicity studies that the most toxic form of the antibiotic is the aggregated state [23,24]. It has been reported that small aggregates, as small as dimers, of AmB are required to induce a cooperative association between it and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…This important clinical drug induces differential membrane permeability changes in ergosterol-and cholesterol-containing fungal and mammalian cells, respectively (reviewed in [34,35]). The Langmuir monolayer studies were of help in understanding the mechanism of a higher affinity of AmB towards ergosterol as compared to cholesterol (which has been confirmed both in mixed monolayers [24][25][26] and in penetration experiments [22,32], and to get insight into the reduced toxicity of liposomal formulations of AmB [5,36].…”
Section: Introductionmentioning
confidence: 90%